Financial Risks, Bankruptcy Probabilities, and the Investment Behaviour of Enterprises - Kai Kirchesch (Hamburg Institute of International Economics (HWWA), 2004)
The link between investment and finance usually enters the empirical literature in the form of financial constraints which are defined as the wedge between the costs of internal and external finance or as the risk of being rationed on the credit market. In this context, the sensitivity of investment with respect to single internal or external finance indicators is assumed to be appropriate to proxy for these constraints. However, enterprises that rely on external funds do not only face this external finance premium and potential borrowing limits, but also the risk of not being able to meet their repayment obligations and thus the risk of bankruptcy. If the risk of bankruptcy enters the profit maximization of the firm, the resulting empirical investment function includes the probability of survival as an additional explanatory variable. This modified neoclassical investment equation is tested with West German panel data which include more than 6000 enterprises and cover a period of 12 years. The empirical results confirm the assumption that the risk of bankruptcy is an important determinant of the enterprises' investment behaviour. Additionally, the results raise the question whether financial constraints respective cash flow sensitivies are the appropriate way to test for the influence of the financial sphere on the investment decisions of enterprises, or whether bankruptcy probabilities better account for these potential financial risks.
Keywords: D92; E22; C23; G33; 330; Investment; Bankruptcy; Financial Constaints; GMM; Konkurs; Investition; Verschuldungsrestriktion; Schätzung; Deutschland